POLITICAL RELATIONS OF THE PEOPLE’S SOVIET REPUBLIC OF BUKHARA WITH TURKEY - Nuridinov Turdali Qambarovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article highlights the history of political relations between the Bukhara People’s Soviet Republic and the Republic of Turkey in the 20s of the twentieth century. The government of the Young Bukharians headed by F. Khodjaev considered political relations with Turkey one of the important directions. The Turkish state was the first to recognize the independence of the BNSR and sent ambassadors to Bukhara. On the basis of archival documents, it is revealed that political relations between the two countries were not effective enough under the pressure of the Soviets.